SOCIAL COGNITION IN PATIENTS WITH PARKINSONˈS DISEASE AND IMPULSE CONTROL DISORDERS - Pančurov, Aleksandra; Putniković, Dunja; Dragašević-Mišković, Nataša (Medicinski podmladak, 2024)
Introduction: Parkinson’s disease (PD) is a slowly progressive degenerative disease characterized by tremor, rigidity, bradykinesia and postural instability. The pathogenesis of PB is characterized by neurodegeneration of dopaminergic neurons. The prevalence is 1% in the population over 60 years. Chronic use of antiparkinsonian therapy leads to psychomotor and autonomic complications. Impulse Control Disorders (ICDs) are described as the inability of a person to resist an impulse or aspire to a particular behavior that harms that person or their environment and impairs their daily functioning. Social cognition is the ability to make inferences about another person through the perception of their emotions and current mental state. Aim: In our study, we examined the social cognition in patients with Parkinson’s disease between those with ICD and those without ICD. Material and methods: The study involved 24 patients diagnosed with Parkinson’s disease, of which 13 patients had ICD while 11 patients did not have ICD. Participants were diagnosed and tested at the Clinic of Neurology at the University Clinical Center of Serbia. The used tests are the Reading the Mind in the Eyes Test (RMET) and the Faux-Pas Recognition Test adapted to the Serbian language. Results: By testing the difference between the group of patients with and without ICD, no statistically significant difference was found in terms of age, sex, duration of disease, presence of motor complications and treatment with levodopa, dopamine agonists or amantadine. Statistically significant difference was found in the achievements on social cognition tests between patients with PD and healthy controls. Conclusion: A statistically significant difference was found in the achievements on social cognition tests between patients with PD and healthy controls.No statistically significant difference was shown in the achievements on the tests of emotional recognition and tests of the theory of mind between the group of patients who had ICD and those without ICD.